Antimicrobial and cytotoxic potential of Dianthus basuticus used in Basotho traditional practice - Lamula, S. Q. Njabulo; Ashafa, A. O. Tom (Bangladesh Journal of Pharmacology, 2014)
The antimicrobial potential of Dianthus basuticus extracts were investigated using 96 wells microplate against selected bacteria and fungi strains while the cytotoxicity was assessed using brine shrimp lethality assay. All the extracts except water inhibited both Gram negative and Gram positive bacteria with the minimal inhibitory concentrations (MIC) ranging from 1.56 to 6.25 mg/mL, except Escherichia coli, Proteus vulgaris and Shigella sonnei that were inhibited at 12.50 mg/mL by dichloromethane extract. Similarly, the acetone and ethanol extracts suppressed the growth of Candida rugosa, C. neoformans, C. albicans and Trichophyton mucoides with the MIC ranging from 1.56 to 6.25 mg/mL. The ethyl acetate fraction of the hydro-alcohol extract inhibited most of the bacteria and fungi at 0.78 mg/mL. The cytotoxicity assay results showed that both hydro-alcohol and ethanol extracts had toxic effect on the brine shrimp larvae with the LC50 values of 17.29 µg/mL and 59.42 µg/mL respectively, while the phytochemical analysis revealed the presence of alkaloids, tannins, saponins and cardiac glycosides. The results confirms moderate to potent antimicrobial activity of D. basuticus.